Implementation of EEDC for Trailer Segment in Enhanced FPGA-based FlexRay Controller - Serfa Juan, Ronnie O.; Kim, Hi Seok (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
FlexRay is a time-triggered protocol that is a standard for reliable high-speed communications network especially for automotive applications such as Advanced Driver Assistance Systems (ADAS). This paper implemented using field-programmable gate array (FPGA)-based communication controller with a reconfigured trailer segment for a faster data rate. The FlexRay's trailer segments that use enhanced error detections and corrections codes that provide better functionality. This paper is implemented and verified using a Xilinx Spartan 6 FPGA. Experimental results show that this proposed implementation performs better regarding data rate and reduction of resource utilisation. This implementation represents an advancement in the FPGA-based system for vehicular applications and other time-triggered devices.